2020
DOI: 10.1177/0095798420971388
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic-Racial and Religious Identity as Mediators of Relations Between Ethnic-Racial Socialization and Prosocial Behaviors Among Black Young Adults

Abstract: Scholars have long asserted the importance of studying cultural socialization processes predicting prosocial behaviors, but studies on this topic among Black young adults are rare. The current study examined the mediating roles of ethnic-racial identity and religious identity in associations between ethnic-racial socialization and prosocial behaviors among Black young adults. Participants consisted of 208 Black young adults ( Mage = 19.90 years, SDage = 1.62, 73.6% women) from universities across the United St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…For example, the participants understood prosociality as a cultural value of the Black community and a means to community cohesion (“It’s just the way we were brought up”). These findings recall previous studies illustrating the contribution of racial socialization messages to prosociality (Lozada et al., 2017; Mayia et al., 2021; White‐Johnson, 2012, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…For example, the participants understood prosociality as a cultural value of the Black community and a means to community cohesion (“It’s just the way we were brought up”). These findings recall previous studies illustrating the contribution of racial socialization messages to prosociality (Lozada et al., 2017; Mayia et al., 2021; White‐Johnson, 2012, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…The high prosocial group in the present study reported experiences related to the predictors of REI, discrimination, identity as oppressed, and parental racial socialization. Like others, we also found prosociality was motivated to dispel stereotypes (Mayia et al., 2021) and to contribute to the community (White‐Johnson, 2012, 2015). We originally conceptualized prosocial behaviors as a stage specific outcome, but they can also be seen here as reactive coping mechanisms.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations